Paulo Freire's Problem-Posing Education Analysis for Stunting Prevention Through P5 Program at SMA Negeri 3 Surakarta - Utami, Della Putri; Liestyasari, Siany Indria (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) program which focuses on the development of students' self-development is an effort by schools to overcome the problem of stunting in society. The purpose of this study was to analyze the implementation of the P5 sustainable lifestyle program as problem-solving learning according to Paulo Freire. The method used in this study was qualitative with a descriptive analytical approach. The sampling technique used purposive sampling with informants consisting of the vice principal for curriculum, the P5 coordinator for class XII, and students. Data were obtained through interviews, observations, and document analysis with validity tests using triangulation of source data and methods. This study uses interactive model data analysis from Miles and Huberman through the stages of data reduction, data presentation, then drawing conclusions. The results of this study explain the relationship between the P5 program on the theme of sustainable lifestyle, the topic of spirulina preventing stunting with problem-solving learning. The aspects of problem-solving learning found in this study include education that is oriented towards liberation, critical awareness, and a dialogical approach between teachers and students. These three aspects cover four project stages consisting of the stages of discovering, imagining, doing, and sharing. Each stage of the project leads to a problem-solving process carried out by students and teachers to show that the use of spirulina which is high in protein and fiber in food processing can prevent stunting. In addition, the results of the study also showed that the implementation of Freire's problem-solving learning can also improve social relations between teachers and students, students and students and can improve students' critical abilities in dealing with a problem. At a more advanced stage, this is expected to foster motivation for students to change non-ideal conditions into ideal ones, such as preventing stunting.